1998
DOI: 10.1042/bj3350417
|View full text |Cite
|
Sign up to set email alerts
|

Atypical protein kinase Cλ binds and regulates p70 S6 kinase

Abstract: p70 S6 kinase (p70 S6K) has been implicated in the regulation of cell cycle progression. However, the mechanism of its activation is not fully understood. In the present work, evidence is provided that an atypical protein kinase C (PKC) isotype, PKClambda, is indispensable, but not sufficient, for the activation of p70 S6K. Both the regulatory and kinase domains of PKClambda associate directly with p70 S6K. Overexpression of the kinase domain without kinase activity or the regulatory domain of PKClambda result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 58 publications
0
56
0
Order By: Relevance
“…Atypical PKCs, specifically PKCl and PKCz, have been shown to regulate p70S6K phosphorylation and activity (Akimoto et al, 1998;Romanelli et al, 1999). Depletion of intracellular stores of Ca 2+ has been shown to abolish p70S6K activation, but has no effect on AKT activation (Conus et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Atypical PKCs, specifically PKCl and PKCz, have been shown to regulate p70S6K phosphorylation and activity (Akimoto et al, 1998;Romanelli et al, 1999). Depletion of intracellular stores of Ca 2+ has been shown to abolish p70S6K activation, but has no effect on AKT activation (Conus et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The isoforms are divided into three subgroups; conventional, Ca 2ϩ -responsive PKC, the novel, Ca 2ϩ -unresponsive PKC, and the atypical, Ca 2ϩ -and TPA-unresponsive PKC (52). Recently, p70 S6k has been shown to be regulated by TPA-responsive (16,29) and -unresponsive PKC isoforms (53,54). In addition, it has been reported that PKC isoforms, including ␣, ␤I, and ␥ of conventional PKC, ␦ and ⑀ of novel PKC, and of atypical PKC, are tyrosine phosphorylated and catalytically activated by treatment of cells with H 2 O 2 (55).…”
Section: Role Of H 2 O 2 In P70mentioning
confidence: 99%
“…Both kinases receive an input signal from common effectors of the PI3-K pathway, including PDK1, protein kinase B, PKC, Rac, and CDC42 (1,6,9,32,47,50). However, some differences in the regulation of S6K␣ and S6K␤ have started to emerge.…”
mentioning
confidence: 99%
“…Furthermore, prolonged treatment of cells with PMA, which leads to down-regulation of DAG-activated PKCs, eliminates mitogenic activation of S6K␣ (56,57). Recently, the PI3-K-and PDK1-activated atypical PKC isoforms and have been implicated in the regulation of S6K␣ (1,31,50). Atypical PKCs have been found in complexes with S6K␣, but it is not yet known whether they can directly phosphorylate and modulate the function of S6Ks.…”
mentioning
confidence: 99%